1983
DOI: 10.1159/000156137
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Interorbital Region of Saimiri sciureus

Abstract: The skull of the platyrrhine primate Saimiri sciureus is distinguished by a large interorbital fenestra. Juvenile skulls still show a bony interorbital septum with some small gaps. A morphogenetic study was undertaken to better understand the structures of the interorbital region, which represents a linkage between the base of the braincase and the nasal skeleton. Already in early ontogenetic stages a reduction of the posterior portion of the nasal capsule and of the cartilaginous interorbital septum are obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Indeed, the low strain magnitudes reported here suggest that the interorbital region is not optimally designed to resist feeding forces, and is in fact overdesigned for this role. In support of this argument, the ability of adult Saimiri to resist feeding forces does not seem to be compromised by the bony fenestra in the interorbital pillar (Maier, 1983;Hartwig, 1995).…”
Section: Strain Magnitudes and The Function Of The Medial Orbital Wallmentioning
confidence: 83%
“…Indeed, the low strain magnitudes reported here suggest that the interorbital region is not optimally designed to resist feeding forces, and is in fact overdesigned for this role. In support of this argument, the ability of adult Saimiri to resist feeding forces does not seem to be compromised by the bony fenestra in the interorbital pillar (Maier, 1983;Hartwig, 1995).…”
Section: Strain Magnitudes and The Function Of The Medial Orbital Wallmentioning
confidence: 83%
“…As Hershkovitz (1977) and Maier (1983) noted, Saimiri is quite inappropriate as a model of ancestral platyrrhine facial morphology considering its extreme orbital approximation and uniquely fenestrated interorbital septum. Furthermore, it is now generally accepted that callitrichines represent a secondarily dwarfed lineage (Rosenberger, 1977(Rosenberger, , 1992Ford, 1980;Leuttenegger, 1980;Martin, 1990), calling the "primitive" nature of their craniofacial morphology into question.…”
Section: Sphenoid Sinusmentioning
confidence: 99%
“…Moreover, on developmental grounds Zuckerkandl (1887), Van Gilse (1927), Keith (1948), and Maier, (1983and Maier, ( , 1993and Maier, ( , 2000, among others, argued convincingly that the lamina transversalis posterior of the sphenoid found in strepsirhines and "insectivores," which forms the floor of the sphenoid recess, is homologous with the ossicula Bertini or sphenoidal concha, which forms the inferior border of the sphenoid recess in humans. Both structures represent ossifications of the floor of the cartilaginous posterior nasal cupula, which forms the recessus cupularis ( Fig.…”
Section: Sphenoid Sinusmentioning
confidence: 99%
“…Hershkovitz (1977) argued that thinning of the interorbital septum is typical of small New World monkeys such as Saguinus, and that the condition in Saimiri was not a discrete character but rather an extreme expression along a morphological continuum. Maier (1983) observed that the fenestra develops postnatally, presumably due t o secondary resorption of the septum by the closely apposed musculature of the eye bulbs. This study suggests that the unique approximation of the eyes to the midline results from the large relative brain size of squirrel monkeys and the precocial nature of their prenatal devel-opment.…”
mentioning
confidence: 99%
“…Biegert (1963) laid further theoretical groundwork and suggested that the potential for midline approximation of the orbits was driven by the size of the intervening nasal capsule. Maier (1993) has recently advanced this work in primates and demonstrated that the ossified parts of the nasal capsule become the ethmoid bone and thus do not directly contribute to the formation of the interorbital septum, which is primarily an aspect of the orbitosphenoid (Maier, 1983). Considered broadly, primates with decreased reliance on olfaction develop smaller nasal capsules and thus express a relative narrowing of the interorbital space.…”
mentioning
confidence: 99%